Effect of Mobility on (I-V) Characteristics of Gaas MESFET - M Azizi; C Azizi (Institute of Advanced Engineering and Science, 2017)
We present in this paper an analytical model of the current–voltage (I-V) characteristics for submicron GaAs MESFET transistors. This model takes into account the analysis of the charge distribution in the active region and incorporate a field depended electron mobility, velocity saturation and charge build-up in the channel. We propose in this frame work an algorithm of simulation based on mathematical expressions obtained previously. We propose a new mobility model describing the electric field-dependent. The predictions of the simulator are compared with the experimental data [01] and have been shown to be good.